MOBILE APPLICATION USER INTERFACE & USER EXPERIENCE DESIGN WITH GAMIFICATION AS A SOLUTION TO GADGET DEPENDENCY - Devi, Rya Sandra; Widagdo, Pratama Bayu (LPPM Univ. Ibn Khaldun Bogor, 2025)
Fast technological developments have brought various conveniences to everyday life. However, behind these conveniences, there are serious challenges in the form of increasing dependence on gadgets, especially among teenagers and young adults. Excessive use of devices has a significant impact on psychological, social, and cognitive aspects. This study offers a solution through a visual communication design approach by designing a mobile application with UI/UX design. The design process was carried out using the Design Thinking method, which consists of five stages: empathize, define, ideate, prototype, and test. Gamification was applied as a strategy to increase user motivation, along with the application of the Laws of UX in the creation of the work. This study project produced four UI/UX design pages: home, add activity, statistics, and profile. The app achieved an average success rate of 98.66%, an average missclick rate of 49.8%, and an average time of 41.16 seconds after being tested on 15 users. This study project demonstrates the importance of implementing UI/UX principles in app development.